Working With Type 1 Diabetes: Investigating the Associations Between Diabetes-Related Distress, Burnout, and Job Satisfaction - Cook, Alexandra (Sasha); Zill, Alexander (Frontiers in Psychology, 2021)
The present study investigates the association between diabetes-related distress and work outcomes (burnout & job satisfaction) among employed people with type 1 diabetes. Employed adults with type 1 diabetes (N = 297) completed an online survey. Measures assessed emotional, social, food- and treatment-related diabetes-related distress, burnout, and job satisfaction, as well as the type of insulin treatment. We conducted multiple regression analyses to test our hypotheses. Emotional diabetes-related distress was significantly and positively associated with burnout. Social diabetes-related distress was significantly and negatively associated with job satisfaction. The type of treatment (insulin pen versus insulin pump) had no significant effect on the outcomes. This study sets the stage for research on the interactions between working conditions, work outcomes and illness symptoms, and problems of people with type 1 diabetes, and, generally, employees with chronic illnesses. The findings have implications for individual health and illness management, burnout prevention, and occupational health measures.